The validity and reliability of “The liver disease symptom index 2.0” for Turkish society - Eraydın, Ayten; Akarsu, Mesut; Derviş Hakim, Gözde; Keskinoğlu, Pembe; Ellidokuz, Hülya (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Chronic liver diseases have been shown to adversely affect the quality of life. Standardized tools for patient assessment are of great importance for treatment and follow-up of these patients. In this study, we aimed to determine the validity and reliability of the Liver Symptom Index 2.0 (LDSI 2.0) for Turkish society, for use in other studies and in daily clinical practice. Materials and Methods: A total of 308 patients with chronic liver disease attending to the outpatient liver clinic of the Department of Gastroenterology, Faculty of Medicine, Dokuz Eylül University between September 2011 and May 2012 were included in this study. A sociodemographic data questionnaire, the LDSI 2.0 comprising 24 items, and the Short Form-36 (SF-36) were completed by the participating patients. After 6 weeks, these tools were re-administered to a total of 115 patients. After obtaining the required permissions, LDSI 2.0 was translated into Turkish using the translation/re-translation method. Results: Of the 308 participants, 160 (51.9%) were male and 184 (43.1%) were female, with an average age of 48.67±13.31 years. Of all cases, 70.5% had viral hepatitis. The average Child-Pugh score was 5.9±1.2, and the average Model For End-Stage Liver Disease (MELD) score was 10.2±3.2. The assessment tool comprised the following sub-items: itching, joint pain, abdominal pain, sleepiness, worry, appetite, depression, fear, jaundice, memory, personality, financial status, use of time, sexual desire, and sexual activity. For more than 50% of the patients, worry (68.8%), depression (65.3%), joint pain (62.3%), itch (56.5%), sleepiness (54.2%), memory problems (53.6), and sexual problems (50%) were present. The internal coefficient of consistency (Cronbach alpha coefficient) was 0.908, which indicates a very high level of consistency. The correlation coefficient for the intraobserver test/re-test reliability was 0.746 (p<0.000), which denotes a significant and good level of reliability. The construct validity between each sub-item of the tool and sub-items of SF-36 was assessed using Spearman’s correlation test, which showed a weak to moderate correlation (<0.04 and 0.4-0.7) in the reverse direction. Conclusion: Our study findings provide supportive evidence of the reliability of the assessment tool. Its validity is similar to the original construct validity and was confirmed in our sample. Therefore, it was concluded that LDSI 2.0 was an appropriate tool for daily clinical use and research purposes. Simultaneous use of this life-quality assessment tool and SF-36 will enable a comprehensive but practical assessment of our patients.